Treinamento resistido e restrição calórica : fatores de proteção cardiovascular em ratas ovariectomizadas - Lino, Anderson Diogo de Souza (Universidade Federal de São Carlos, 2017)
Introduction: Hypertension is an important risk factor for menopausal cardiovascular disease. Resistance training (RT) when associated with the caloric restriction diet (CR) has been shown to have important effects on blood pressure and the aortic artery, minimizing complications due to menopause, such as hypertension. Aim: In this study, we investigated the effects of Ovariectomy and the Resistance Training, Caloric Restriction, and the association of both intervention in systolic blood pressure, matrix metaproteinase-2 activity, aortic vascular reactivity and morphological alterations in ovariectomized Holtzman rats. Material and methods: Fifty female Holtzman rats were subjected to ovariectomy and Sham surgery and distributed into: Sham-sedentary; Ovariectomized-sedentary; Ovariectomized- Resistance Training; Ovariectomized-Caloric Restriction; and Ovariectomized-Resistance Training and Caloric Restriction groups. Resistance Training and 30% Caloric Restriction protocols were performed by 13-weeks. Systolic blood pressure, acetylcholine, and sodium nitroprusside induced relaxation of aortic rings; the hematoxylin-eosin stain used to highlight the aortas wall cross-sectional area and the matrix metaproteinase-2 activity, insulin tolerance test and aorta vessel remodeling were analyzed. Results: We observed that, Ovariectomy increased systolic blood pressure, decreased potency in dependent and independent endothelium relaxation and matrix metaproteinase-2 activity, promoted insulin resistance and aorta vessel remodeling in cross-sectional area, media to lumen ratio, collagen content and alter structure and elastic fibers of the vessel. However, the association of exercise and diet prevent the increase systolic blood pressure, improved the relaxation potency in dependent and independent endothelium relaxation, elevated the matrix metaproteinase-2 activity, increased the aorta cross-sectional area, media to lumen ratio, decreased collagen content and alter elastic fibers in aorta vessel wall. Conclusion: Our study reveled that the association of resistance training and caloric restriction can prevent the hypertensive condition, improve vascular function, activate matrix metaproteinase-2, and produce a beneficial hypertrophic remodeling with increased vascular compliance in ovariectomy in Holtzman rats.
Keywords: Pressão arterial sistólica; Hipertensão; Ovariectomia; Treinamento resistido; Restrição calórica; Tônus vascular; Artéria; Aorta; Systolic blood pressure; Ovariectomy; Resistance training; Caloric restriction; Vascular tonus; CIENCIAS BIOLOGICAS::FISIOLOGIA